News Website Accessibility Evaluation Using Website Accessibility Conformance Evaluation Methodology - Fadli, Muhammad; Suranto, Beni (Department of Informatics Universitas Islam Indonesia, 2024)
News website have become one of the media used to distribute information in line with the large use of the large use of internet. A website must be designed to meet the needs of every users in obtaining information, including people with disabilities as regulated in Act. Number 8 of 2016 article 24. Therefore, an evaluation is needed to measure the level of accessibility of news website pages, where this study uses Detik.com news site as one of the largest media in Indonesia. The evaluation was conducted using the Website Accessibility Conformance Evaluation Methodology (WCAG-EM) to measure the level of accessibility of Detik.com news site according to the Web Content Accessibility Guidelines (WCAG) 2.0 standard with the assistant of AChecker and WAVE evaluation tools. The result shows that none of the pages of Detik.com comply with the WCAG 2.0 minimum accessibility standards. The majority of web pages can not convey the purpose of both text and image links with clear context. Improvements to the accessibility barriers found can be carried out immediately to improve the level of accessibility of Detik.com news site.